KARAKTERISASI BEBERAPA KULTIVAR PADI GOGO LOKAL - Sarwanto, Sarwanto; Samudin, Sakka; Ete, Andi (AGROTEKBIS, 2018)
The aim of the research was to discover the characteristics or the features of several local upland rice cultivars and thesimilarity of the cultivars based on cluster analysis. It was a field research conducted at Sidondo 3 Agricultural ExperimentalStation (BPTP) of Sigi Sub-district of Sigi Biromaru Regencyof Central Sulawesi. The research started in February to June 2016.Cluster analysis was applied to visualize multivariate data on seven cultivar treatments, namely Walnut, Tokalang, Habo, Toni, Jenggi red glutinous rice, Sampar, and Ranta. Each cultivar was grown in a seedbed where then the cultivar was characterized to determineits features and characteristics. Based on the dendogram analysis of the seven local upland rice cultivars, it was found that inthe distance of 15, there are five different cultivars (no genetic relationship), namely Walnut, Habo, Ranta, Tokalang, and Toni. The two cultivars with very close genetic relationship are Jenggi red glutinous rice and Sampara. It is suggested that they from the same male parent. In the distance of 18, there are five cultivars which have a very close genetic relationship, namely Habo, Ranta, Jenggi red glutinous rice, Sampara, and Tokalang.Â  They are most likely from the same male parent.Â Key Words: Characterization, Cluster analysis, and Local upland rice.